Incidence of Dentinal Micro Cracks during Root Canal Preparation with Self Adjusting File, Reciproc Blue, and ProTaper Next - Katanec, Tomislav; MiletiÄ‡, Ivana; BarÅ¡iÄ‡, Gorana; Kqiku-Bliblikaj, Lumnije; Å½iÅ¾ak, Mirza; Krmek, Silvana JukiÄ‡ (Iranian Endodontic Journal, 2020)
Introduction: Forces formed during root canal instrumentation could cause the crack formation in dentinal walls. Their propagation may result in vertical root fracture and eventually tooth loss. The aim of the study was to explore microcrack formation after root canal preparation with Self-adjusting File (SAF), Reciproc Blue (RB), and ProTaper Next (PTN) instruments on young premolars by means of micro-computed tomography. Methods and Materials: Forty-five upper premolars with two canals, were extracted due to orthodontic reasons from patients aged 16 to 20 years and stored for up to two months. The teeth were scanned with a micro-CT (Nikon XT H 225, Tring, UK) at structural resolution of 20.2 µm and randomly divided into three groups: SAF, RB, and PTN. Specimens were instrumented and irrigation was performed with 12 mL of 2.5% sodium hypochlorite (NaOCl) and 4 mL of 17% ethylenediaminetetraacetic acid (EDTA) per root canal. Subsequently, the specimens were scanned under the same conditions as before, in wet condition and 24 h after drying. The presence of microcracks in dentinal walls was evaluated using the image-processing software Volume Graphics VGStudio Max 3. Results: No dentinal defect was found in any evaluated specimen, neither in pre-nor post-operative scans in wet and dry condition. Conclusion: Under the circumstances of this in vitro study instruments with improved design and metallurgy do not cause dentinal microcracks in young premolar teeth. Keywords: Dentin; Micro-computed Tomography; Nickel-titanium; Root Canal Preparation